Penilaian Kinerja Portofolio Menggunakan Sharpe dan Treynor Indeks Pasca Pandemi COVID-19: - - Adilla Zahratul Hilmi; Diah Yudhawati; Asti Marlina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The New Normal era or commonly said to be a new situation after the COVID-19 pandemic has disrupted capital market conditions. Fluctuating stock prices require an investor to be careful in investing their funds. Therefore, it is important to form a portfolio. The study aims to determine the portfolio performance assessment on stocks listed in the IDX Growth30 index during the period February 2022 - January 2023. The type of data in this study is descriptive quantitative data. The data source is secondary data obtained through literature studies and various literature (historical data on closing stock prices and interest rates). The sample withdrawal procedure uses purposive sampling with certain criteria so that 5 companies are obtained as research samples. The results of this study indicate that in the performance assessment using the sharpe index method, the highest performance is in Portfolio I and the lowest performance is in Portfolio III. While the performance assessment using the treynor index method, the highest performance is in Portfolio I and the lowest performance is in Portfolio IV.